Clinically malignant atypical glomus tumour. (3rd January 2013) - Binesh, Fariba; Akhavan, Ali; Zahir, Shokouh Taghipour; Bovanlu, Taghi Roshan
Abstract : Glomus tumours (GTs) resemble the normal glomus body and have a predilection for skin and subcutaneous tissue. Although the majority of glomus tumours are small, benign neoplasms that occur in the dermis or subcutis of the extremities and cases of atypical or malignant variants have been reported. We report a case of a man who presented with a 1-year history of subcutaneous nodule in the right scapular area which was mildly tender. The nodule measured 2 cm. Microscopic examination showed features of glomus tumour with increased mitotic activity. These features, by current definition, would suggest glomus tumour of uncertain malignant potential. Three months later, he presented with recurrence. During his metastasis work-up, we noticed bilateral pulmonary metastasis. Metastasising GTs are rare. The patient underwent wide local excision and received chemotherapy.